Frankenstein - Arneson, D. J.; Shelley, Mary Wollstonecraft, 1797-1851.; Shelley, Mary Wollstonecraft, 1797-1851. (Chicago : Kidsbooks, Inc., 1992)
The monster was supposed to be man's benefactor but, scorned for his ugliness, he swears revenge on his creator and the human race.
Keywords: Frankenstein (Fictitious character) -- Fiction; Monsters -- Fiction; Horror stories